EXTRINSIC AND INTRINSIC MODE OF HYDROGEN OCCURENCE IN NATURAL OLIVINES: FTIR AND TEM INVESTIGATION - Khisina N.R.; Wirth R.; Andrut M.; Ukhanov A.V. (My University, 2001)
Olivine crystals from two mantle nodules in kimberlites (pipe Udachnaya and pipe Obnazennaya, Yakutiya, Siberia) were investigated using EMP, TEM, AEM and FTIR techniques to determine the mode of hydrogen occurrence in olivine. Olivine contains three types of nanometer-sized inclusions: “large” inclusions of hexagonal-like shape up to several hundred nm in size (1), lamellar defects (2) and small inclusions of hexagon-like shape up to several 10 nm in size (3). Lamellar defects and small inclusions are considered to be a “hydrous” olivine. All three types of inclusions contain OH− or water, but they are different with respect to their phase composition. In “large” inclusions (1) hydrous magnesium silicates, such as serpentine + talc (“kerolite”?) and 10-Å phase + talc were identified. Lamellar defects (2) and small inclusions (3) are depleted in Mg and Fe compared to the olivine matrix, while the silica content is the same as that of olivine. Modulations in the periodicity of the olivine structure are observed in SAED patterns and HREM images of (2) and (3). The superperiodicity can be referred to OH−-bearing point defect ordering in the olivine structure. If this is the case, the material of both lamellar defects and small inclusions can be assumed to be a “hydrous olivine” Mg2–x v x SiO4H2x with a cation-deficient olivine crystal structure. Thus, both an extrinsic mode of hydrogen occurrence in olivine, such as nanometer-sized inclusions of OH−-bearing magnesium silicates, and an intrinsic mode of hydrogen incorporation into the olivine structure, such as “hydrous olivine” in itself, were found. The data obtained here show that the OH absorption bands observed in olivine spectra at 3704(3717) and 3683(3688) cm−1 can be unambiguously identified with serpentine; the band at 3677(3676) cm−1 can be associated with talc. The absorption bands observed at 3591 and 3660 cm−1 in olivine match those of the 10-Å phase at 3594, 3662 and 3666 cm−1.